The effectiveness of bus system in Universiti Teknologi MARA / Dayangku Salma Awang Ismail - Awang Ismail, Dayangku Salma (2005)
The rapid progress of science and technology does not change how the way people to move from one destination to another destination; by using transport. Bus transportation is one of the mode transportation that regularly used by the public. The public prefer to use bus rather than private cars as to minimize the expense on travel cost. The effectiveness of bus system relies on bus services and bus operations and also its additional service as well. Nowadays, many effort have been implemented and recommended in order to increase the effectiveness of bus system. This project is to study on the Effectiveness of Universiti Teknologi MARA (UiTM) bus system in order to increase the efficiency of UiTM campus bus. The main purpose of this study is to evaluate the effectiveness of UiTM bus system and also determine the factors that may contribute to its weakness. From the study, it can be conclude that the effectiveness of UiTM bus system can be improved by implementing effective strategies to cater its weakness. Beside, by conducting bus stop survey and running bus survey, the factors that contribute to less convenient of UiTM bus system are insufficient frequency of bus operated and longer time travel for a trip of bus.